Characterization of Molecular Properties and Expression of Gene GmPLMT and Its Effects on the Production of Lipid Metabolites in Soybean and Arabidopsis thaliana - Zhanyu Chen; Yushuang Wang; Yanbo Chen; Xiaoqin Yang; Shuang Wang; Tingting Yu; Ying Zhou; Xiyan Cui (Agronomy, 2021)
Phospholipid N-methyltransferase (PLMT) plays an important role in the synthesis of phosphatidylcholine (PtdCho). The aim of this study was to characterize the molecular properties of GmPLMT and the expression of soybean GmPLMT and its effects on the production of lipid metabolites. Results showed that GmPLMT composed of mainly α-helix was a hydrophobic and transmembrane protein. In soybean leaves, GmPLMT was highly expressed during seedling and flowering stages. In transgenic Arabidopsis thaliana, the highest and lowest expression levels of GmPLMT were detected at flowering and maturity stages, respectively. The total phospholipid contents in soybean grains were decreased from 7.2% (35 days after flowering) to 4.8% (55 days after flowering) and then increased to 7.0% (75 days after flowering). The contents of PtdCho showed a similar pattern to that of total phospholipids. In transgenic A. thaliana seeds, the contents of total phospholipids and PtdCho were significantly increased. Significantly positive correlations were revealed between expression of GmPLMT and contents of both PtdCho and crude fats, and between the contents of PtdCho and both linoleic acid and linolenic acid, suggesting that increased expression of GmPLMT improved the production of lipid metabolites. This study provided solid experimental evidence for further improvement of soybean quality based on GmPLMT in the molecular breeding of soybeans.